POLÍTICA MARANHENSE DE INCLUSÃO ESCOLAR: com a palavra, as professoras - Coelho, Washington Luis Rocha (2008)
The pertaining to school inclusion of the people with deficiency in the regular net of education deserves deepened analyses, due to the innumerable fidgets and reflections of the professors, who from its experiences make pertinent considerações to the educational politics. This work had as objective to analyze the perceptions of the professors of the special education on the maranhense politics of pertaining to school inclusion of the state net of education in São Luís - MA, in the period of 2003 the 2006. For the collection of data bibliographical survey and research of field had been used. The research sources had understood the theoretical referenciais of the special education and pertaining to school inclusion, where they had been appropriate legal the level that deal with the special education and other documents as reports, projects and gotten plans of action in the State secretary of the Education - SEDUC and Supervision of Special Education - SUEESP. The instruments for the collection of data had been interviews half-structuralized with 29 teachers of the educandos with auditory deficiency, intellectual and visual taken care of in the classrooms special and rooms of resources. The gotten results signal for efetivacion of the politics of inclusive education in the maranhense state net in what it says respect to the concretion of actions directed toward the teaching qualification, offers of the specialized educational attendance, structural improvements in the physical conditions, architectural and of the pertaining to school units, that if present inadequate, with scarcity of didactic resources and inefficiency of the equipment specific and specialized and joint with the too much public sectors in the implementation and improvement of educational the public politics.